A Pragmatic Guideline for Evaluation of Social Intervention - Herrera Sánchez, Isabel María; León Rubio, José María; Medina Anzano, Silvia (The Spanish Journal of Psychology, 2005)
Considering the many theoretical and methodological viewpoints in the field of evaluation, a guideline was established to facilitate the evaluation of social intervention programs. For this purpose, the goals of the evaluation were taken into account: (a) planning interventions, (b) learning and continuous improvement of interventions, (c) programming policies, and (d) transformation of society. These goals will determine the perspective of the analysis selected (focusing on the evaluand or the context) and the strategies for change employed (focusing on processes or results). The elements that, according to Shadish, Cook, and Levinton (1991), constitute the theory of evaluation (evaluand, value, building of knowledge, and uses) have also been considered. The analysis of all these components led to the elaboration of a guideline to orient the practice of evaluation from a pragmatic perspective, in accordance with the demands and needs of a certain social context.